Considerations on the flow configuration of membrane chromatography devices for the purification of human basic fibroblast growth factor from crude lysates. Issue 8 (12th August 2016) - Gieseler, Gesa; Pepelanova, Iliyana; Meyer, Annette; Villain, Louis; Beutel, Sascha; Rinas, Ursula; Scheper, Thomas
Abstract : Membrane chromatography possesses numerous advantages such as operation at high flow rates, low back pressure, ease of handling and scale up, which make the membrane adsorber process a viable alternative to conventional packed column chromatography. A purification process for the isolation of human recombinant basic fibroblast growth factor (FGF‐2) based on membrane chromatography was investigated using devices with different flow configurations. In the first process, the FGF‐2 capture step was performed with an axial flow device, while the alternative method achieved direct capture of FGF‐2 from unclarified cell lysate with a tangential flow device. In both processes, FGF‐2 purities exceeded 82% and the purified cytokine displayed high biological activity. Binding capacity (BC) from fermentation broth of the axial flow device was 28 mg/mL. This was 50% higher than the BC obtained with the tangential flow device under particle‐free supernatant conditions (18 mg/mL) and 150% higher compared to the BC achieved with unclarified cell lysate (11 mg/mL). While membrane chromatography in tangential flow mode omits clarification and thus reduces the number of stages in the downstream process, it displays lower peak resolution and leads to a lower overall process yield.